1992
DOI: 10.23986/afsci.72445
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chloride and nitrogen on nitrate accumulation and yield in beetroot (Beta vulgaris var. conditiva)

Abstract: A pot and a field experiment were conducted to evaluate the effects of different nitrogen and chloride fertilizer levels on the nitrate content of beetroot. The yield and dry matter content were also determined. Sulphate fertilization was used as a control to chloride fertilization. There was a considerable decrease in the nitrate content of beetroots during the growing season. High nitrogen fertilization caused nitrate accumulation in both experiments. Chloride had a significant decreasing effect on the nitra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…how to optimize cropping practices, since some practices can affect yield and quality in opposite directions. N fertilization significantly increases yield, but can also decrease quality through excessive nitrate content and reduce soluble solids content (Becker, 1989;Lee et al, 1971;Peck et al, 1974;Salo et al, 1992). The objective of our study was to provide data as a basis for optimizing fertilization, cultivar selection, and sowing date with respect to the yield and quality of table beet.…”
mentioning
confidence: 99%
“…how to optimize cropping practices, since some practices can affect yield and quality in opposite directions. N fertilization significantly increases yield, but can also decrease quality through excessive nitrate content and reduce soluble solids content (Becker, 1989;Lee et al, 1971;Peck et al, 1974;Salo et al, 1992). The objective of our study was to provide data as a basis for optimizing fertilization, cultivar selection, and sowing date with respect to the yield and quality of table beet.…”
mentioning
confidence: 99%
“…Kadar and Erno (2000) reported that for the Beta vulgaris L. the optimal values of soil are 200 mg K 2 0 kg -1 and 150-200 mg P 2 0 5 kg -1 . Some authors (Michalik and Grzebelus, 1995;Ugrinovic, 1999) reported that the dry weight content in storage root varied from 80 to 164 g kg -1 and was decreased by nitrogen abundance (Michalik and Grzebellus, 1995;Salo et al, 1992). A number of papers (Stopar el al., 1988;Salo et al, 1992;Goh and Vityakon, 1983;Cerne, 1981;Fritz et al, 1989;Vogel, 1996) deal with the influence of nitrogen fertilization (from 120 to 600 kg N ha -1 ) on the red beet yield (from 20 to 70 t ha -1 ).…”
Section: Introductionmentioning
confidence: 99%